Microstructure Analysis and Surface Planarization of Excimer-laser Annealed Si Thin Films - Yu, Miao (2020)
The excimer-laser annealed (ELA) polycrystalline silicon (p-Si or polysilicon) thin film, which influences more than 100-billion-dollar display market, is the backplane material of the modern advanced LCD and OLED products. The microstructure (i.e. ELA microstructure) and surface morphology of an ELA p-Si thin film are the two main factors determining the material properties, and they significantly affect the performance of the subsequently fabricated thin film transistors (TFTs). The microstructure is the result of a rather complex crystallization process during the ELA which is characterized as far-from-equilibrium, multiple-pulse-per-area and processing-parameter dependent. Studies of the ELA microstructure and the surface morphology closely related to the device performance as well as the microstructure evolution during the ELA process are long-termly demanded by both the scientific research and the industrial applications, but unfortunately have not been thoroughly performed in the past.